Ownership, capital structure and firm performance : evidence from Malaysia - Rafik,Timezghine Mohammed (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2014)
Corporate governance in the Asian context has witnessed a critical review and investigation from scholars after the Asian Financial crisis in 1997. This is due to the negative effect of ownership structure, which is concentrated, on minority shareholders. Previous studies considered this problem and tried to propose solutions and proposals to come up with efficient corporate governance mechanism. It has been argued that environment with weak legal protection of minority shareholders and inefficient external market and financial institutions is associated with concentrated ownership structure. Literatures in this context provided contradicted arguments about the effect of concentrated ownership in ensuring efficient corporate governance practice and better firm performance. Earlier studies claimed that dispersed ownership is the most efficient structure, where recent studies argued that block holders, such as families state and foreign, showed better governance practice and better firm performance. Within this debate this study tried to contribute to the literature by evaluating the corporate governance practice in Malaysia by focusing on ownership structure and its effect on firm performance and including a new factor, capital structure, to investigate its potential effect on the governance, and taking agency theory as un underlying theoretical background to explain the relationships. Malaysian firms are characterized with concentrated ownership which provides better environment to conduct this study. Based on data collected from the top 100 largest listed companies in Bursa Malaysia, our results showed that after nearly 15 years from the Asian Financial crisis concentrated ownership is still an important component in the Malaysian firms' ownership structure. The results showed further that managerial ownership and leverage are two governance mechanisms which are not used efficiently in governance. Panel Data analysis showed that ownership structure has different relationships with firm performance measurements, negative with the market based measurement (Tobin's Q), and positive with accounting based measurement (ROA), which indicate for potential expropriation of minority shareholders; where managerial ownership recoded negative relationships with both measurements. Foreign and state ownership have positive association with firm value, but state ownership is insignificant, whilst all ownership types are positively related with profitability. By including leverage as a moderating variable the results showed that moderating effect is significant and implies that leverage should be considered as an efficient corporate governance mechanism to ensure better performance and low agency problem.